Kepuasan Pelanggan Ditinjau Dari Kualitas Pelayanan, Kepercayaan Dan Inovasi Produk (Studi Pada Pelanggan J&T Ekspress Purwosari) - Yufi Nuresa (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study was to determine customer satisfaction J&T Express Purwosari in terms of service quality, trust and product innovation. In this study, the authors used a descriptive quantitative approach. The population in this study were all customers of J&T Ekspress Purwosari totaling 1958 people, the sample used in this study was 100 people. The results of this study have a significant effect both partially and simultaneously between Service Quality, Trust and Product Innovation on Customer Satisfaction J&T Express Purwosari. Keywords: Customer Satisfaction, Service Quality, Trust and Product Innovation.